Transformasi Kepedulian Mahasiswa Terhadap Hewan Melalui Pengalaman Kuliah Lapangan - Setiadi, Anandita Eka; Suwono, Hadi; Ibrohim, Ibrohim (Jurnal Biotek, 2025)
Field study is a learning activity that provides authentic experiences to interact directly with animals in an environment. This experience can trigger changes in perspective and internalization of new values, including animal awareness. This study aims to analyze the transformation of students' awareness of animals after participating in a field study. The study used a qualitative descriptive approach with a case study design. The subjects were students of the Biology Education program at Universitas Muhammadiyah Pontianak who had participated in a field study in the Animal Taxonomy, Ecology, and Herpetology courses. Data were collected through open questionnaires and analyzed using thematic analysis techniques. The results showed that the field study significantly impacted changes in students' perceptions, attitudes, and behaviors in the context of animal conservation. Through direct interaction with nature and society, the contextual learning process has encouraged students to reflect deeply, reassess old assumptions, and experience personal transformation. Students not only gain a more concrete scientific understanding of endemic species and ecological conditions, but also experience strengthening of the values of empathy, responsibility, and active involvement in environmental issues. This finding aligns with the theory of transformative learning, where the stages of self-examination, critical reflection, and intentional action have been proven to be achieved in the field lecture process